Blue and white delicate porcelain and preparation method thereof
Patent Information
- Application Number
- CN202611393076.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]针对现有技术中玲珑眼色调单一、通透性差、成品率低的技术缺陷,本发明提供一种青花玲珑瓷及其制备方法
本发明将着色剂封装于硼锂硅酸盐玻璃基质中,可做到其在煅烧过程中适时释放,均匀显色,且各个玲玲眼中颜色互不相同且无干扰。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic technology, specifically relating to a blue-and-white openwork porcelain and its preparation method. Background Technology
[0002] Flower-patterned openwork porcelain is one of the four famous traditional porcelains of Jingdezhen. Its production process involves carving intricate patterns into the unglazed body, filling it with a special openwork glaze, combining it with flower designs, applying a transparent glaze, and then firing it once at high temperature. After firing, the openwork glaze creates a semi-transparent "glass window" effect, allowing light to pass through while preventing liquid leakage. This effect, combined with the cobalt blue hue of the flower patterns, results in a piece with extremely high artistic value.
[0003] However, there are still some prominent problems in the existing process of preparing blue and white openwork porcelain. For example, the existing openwork eye color is a single, headless, transparent, and emerald green, which is difficult to meet the needs of modern consumers for color diversity. After the introduction of metal coloring oxides, the viscosity of the existing colored openwork glaze increases at high temperatures, making it difficult to remove bubbles. This results in the openwork eye appearing milky or semi-milky, and the light transmittance is generally not high. Because the expansion coefficients of the body, the openwork glaze, and the surface glaze are difficult to match, the openwork eye is very prone to cracking, peeling, or stress cracking during the firing process, resulting in a low average yield in the industry. Although patent CN101875567B discloses a technique for improving the transparency of Linglong glaze by introducing rare earth elements such as Y2O3 and Rb2O, it is still a single color tone and does not solve the problem of matching the expansion coefficients of the body and glaze. Patent CN110981417B discloses a method for preparing polychrome Linglong porcelain, which uses sandblasting to make Linglong holes and fill them with colored Linglong glaze. However, the pigments are directly mixed into the glaze, resulting in problems such as uneven pigment distribution, harsh color transitions between adjacent Linglong holes, and insufficient transparency. Moreover, the yield is still not ideal.
[0004] Therefore, developing a blue-and-white openwork porcelain preparation process that can achieve a multi-color effect of the openwork eye on the same object, and has high transparency and yield rate, can meet the needs of contemporary consumers. Summary of the Invention
[0005] In view of the technical defects of existing technologies, such as the single color tone, poor transparency, and low yield of openwork porcelain, this invention provides a blue and white openwork porcelain and its preparation method.
[0006] The purpose of this invention is to provide a method for preparing blue and white openwork porcelain, the method comprising the following steps: Step 1: Prepare ceramic body clay and roll it into a green body; the body clay, by weight, includes 40-55 parts kaolin, 15-20 parts quartz, 15-20 parts potassium feldspar, 3-5 parts talc, and 4-8 parts β-nepheline; the β-nepheline has a D... 50≤1μm. Introducing β-nepheline (Li2O·Al2O3·2SiO2) into conventional ceramic body raw materials, which has a zero or negative coefficient of thermal expansion, can adjust the coefficient of thermal expansion of the body to be closer to that of the Linglong glaze, thereby reducing the cracking phenomenon of Linglong eyes after firing and cooling and improving the yield. Step 2: After the blank is naturally air-dried, use a mold to press out delicate eye holes in one go, and carve micro grooves on the surface of the hole wall. Then fire it at 650-850℃. Step 3: Prepare the delicate glaze paste and fill the delicate eye holes. After filling, use ultrasonic-assisted vacuum degassing to achieve a smooth glaze surface. The raw material components of the delicate glaze paste, by weight, include 18-22 parts potassium feldspar, 18-22 parts sodium feldspar, 12-16 parts quartz, 10-20 parts kaolin, 6-10 parts light calcium carbonate, 4-6 parts calcined zinc oxide, 3-6 parts calcined boron oxide, 5-8 parts borax, 3-5 parts lithium carbonate, 0.5-2 parts yttrium oxide, 0.3-1.5 parts hafnium oxide, and 0.8-2 parts coated pigment particles. To ensure the transparency and low coefficient of expansion of the Linglong glaze, the composition of the Linglong glaze is optimized. Potassium feldspar and sodium feldspar are used as base solvents, and quartz is used as a framework in conjunction with lithium carbonate to reduce the coefficient of expansion of the Linglong glaze and form a pressure protective layer. Light calcium carbonate can improve the hardness and gloss of the glaze surface. Zinc oxide promotes the expulsion of bubbles and promotes fusion. Boron oxide assimilates and fuses with the glass matrix in the coated pigment particles to avoid scattering. Yttrium oxide inhibits the formation of the main glass phase, and hafnium oxide changes the glass crystallization temperature. The two work together to inhibit the formation of crystal nuclei and ensure the high transparency of the glaze layer. Step 4: Apply a transparent glaze to the inner and outer surfaces of the body. The raw material components of the transparent glaze, by weight, include 20-25 parts potassium feldspar, 20-25 parts sodium feldspar, 15-20 parts quartz, 8-14 parts kaolin, 5-8 parts light calcium carbonate, 3-5 parts calcined zinc oxide, 4-6 parts borax, and 1-2 parts lithium carbonate. The raw materials used for the glaze are similar to the base materials of Linglong glaze, and their coefficients of thermal expansion are similar, which is beneficial for buffering thermal stress. Step 5: Draw blue and white patterns on the surface of the blank; Step Six: Fire the green body once at 1250-1320℃; Among them, the difference in the coefficient of thermal expansion among the body, the transparent glaze, and the openwork glaze is ≤0.3×10. -6 / ℃.
[0007] This invention optimizes the composition of the clay body, the glaze, and the transparent glaze, thereby controlling the difference in the coefficients of thermal expansion between the clay body, the glaze, and the glaze to ≤0.3×10⁻⁶. -6The temperature of ℃ can effectively prevent cracking at the edge of the glaze, while ensuring good fusion, transparency, and high yield among the glaze layers. Furthermore, by optimizing the preparation process, microgrooves are designed on the pore walls of the glaze to further improve the quality of the glaze, and the colorant is made into coated particles to improve the uniformity and non-interference of the colorant in the subsequent process. The resulting blue and white glaze with glaze has multiple colors and good transparency, and a high yield.
[0008] Preferably, in step three of the above technical solution, the outer diameter of the "delicate eye" hole is 8-12 mm, the inner diameter is 2-5 mm, and the depth of the microgrooves is 30-60 μm, the width is 50-80 μm, and the spacing is 150-200 μm. In this technical solution, by designing the "delicate eye" hole structure and setting the inner and outer diameters of the holes to different sizes to form an inclined surface, not only can the cross-sectional area of the delicate glaze and the body be increased, improving adhesion, but stress concentration can also be avoided. The radial microgrooves on the hole walls not only facilitate the removal of air bubbles but also further increase the bonding between the delicate glaze layer and the body, enhancing adhesion, reducing crack formation, and greatly improving the yield.
[0009] Preferably, in step three of the above technical solution, the coated colorant particles are composed of a colorant encapsulated in a boron-lithium silicate glass matrix; the chemical composition of the boron-lithium silicate glass matrix, by mass percentage, is: SiO2 45-55%, Al2O3 12-19%, B2O3 5-10%, CaO 3-12%, ZnO 5-12.5%, Li2O 1-3%, Na2O+K2O 2-8%, and the particle size D 50 The particle size is 0.5-1.5 μm. In this technical solution, the colorant is encapsulated in a boron-lithium silicate glass matrix, which fuses with the Linglong glaze during firing and is uniformly released into the glaze layer, achieving the goal of different Linglong glaze layers having different colors without interference. The boron-lithium silicate glass matrix used has SiO2 as the main raw material to ensure structural stability. The added Al2O3 can further improve chemical and thermal stability. The added B2O3 can lower the pre-melting temperature of the coated colorant particles and match with the boron oxide in the subsequent Linglong glaze, which is conducive to fusion. The added CaO adjusts the glass softening point, allowing it to melt with the Linglong glaze at the appropriate time. The added ZnO further improves chemical stability and synergistically promotes interfacial fusion with the same components in the Linglong glaze. The added Li2O can further lower the pre-melting temperature and promote rapid diffusion. The added Na2O+K2O is used to adjust the melting rate and improve gloss.
[0010] Preferably, in the above technical solution, the colorant is selected from at least three of the following, and each colorant is independently coated: Royal Blue: Co-Al pigment; Emerald Green: Zr-Si-Pr-V pigment; Golden yellow: Zr-Si-Pr pigment; Pale yellow-green: V-Zr-Si pigment; Bright yellow: Ti-Ni pigment.
[0011] Preferably, in step three of the above technical solution, the preparation process of the Linglong glaze paste is as follows: the colorant and boron lithium silicate glass matrix raw material are mixed at a mass ratio of 2-10:90-98, pre-melted at 950-1150℃ for 1-2 hours, quenched in water and then pulverized to obtain coated colorant particles; the obtained coated colorant particles are added to the base glaze paste formed by other raw material components of the Linglong glaze paste, and stirred at 200-300 rpm for 20-30 minutes to obtain the final product.
[0012] Preferably, in step three of the above technical solution, the ultrasonic-assisted vacuum degassing process is as follows: the blank filled with glaze is placed in a vacuum environment of ≤5Pa, and ultrasonic treatment at 20-40kHz is applied for 10-20 minutes. Ultrasonic cavitation can break the surface tension film of bubbles, and the high vacuum can cause microbubbles to expand and escape, thus completely removing the bubbles.
[0013] Preferably, in step six of the above technical solution, under a reducing atmosphere (CO 2-4%), the firing process employs a gradient heating / cooling process, specifically as follows: Room temperature - 600℃: heating rate 80-120℃ / h; removes residual moisture and prevents cracking; 600-900℃: Heating rate 150-200℃ / h; Combustion of organic matter and removal of structural water can prevent the formation of bubbles after subsequent glazing; 900-1250℃: Heating rate 180-220℃ / h; to densify the initial green body; 1250-1320℃: Heating rate 40-80℃ / h; Maintain heat at 1320℃ for 30-40 minutes; display colors evenly. 1320-800℃: Cooling rate 100-150℃ / h; rapid pre-cooling allows the glaze to solidify quickly and lock in the color; 800-400℃: Cooling rate 20-30℃ / h; slow pre-cooling, volume shrinkage as crystal form transforms, thermal stress is fully released; 400-80℃: Cooling rate 80-120℃ / h, rapid cooling, no subsequent crystal form transformation, which can significantly shorten the process.
[0014] The present invention also provides a blue and white openwork porcelain prepared by the above preparation method.
[0015] Advantages compared to existing technologies: This invention encapsulates the colorant in a boron-lithium silicate glass matrix, which allows it to be released at the right time during calcination, resulting in uniform color development, and ensuring that the color is different in each child's eyes without interference.
[0016] This invention optimizes the formulations of the body raw materials, surface glaze raw materials, and linglong glaze raw materials, matching the difference in their coefficients of thermal expansion to ≤0.3×10. -6 / ℃ can effectively prevent cracking at the edge of the delicate eye, while also ensuring good fusion between the glaze layers, high transparency, and high yield.
[0017] This invention improves the adhesion between the glaze layer and the body by designing the structure of the "delicate eye" pattern, effectively preventing cracking of the "delicate eye" pattern and further improving the yield.
[0018] The blue-and-white openwork porcelain obtained by this invention achieves multiple colors in the same piece, with good transparency, high yield, and can be mass-produced industrially, possessing both artistic and economic value. Detailed Implementation
[0019] The above-described technical features of the present invention and the technical features specifically described below (such as in the embodiments) can be combined with each other to form new or preferred technical solutions. However, the present invention is not limited to these embodiments, nor are these embodiments limited in any way.
[0020] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the formulations involved in the following examples are all commercially available products that can be purchased from the market.
[0021] The present invention will be further described in detail below with reference to embodiments: Example 1 A method for preparing blue and white openwork porcelain includes the following steps: Step 1: Mix the following materials by weight: 40 parts kaolin, 18 parts quartz, 18 parts potassium feldspar, 4 parts talc, and β-nepheline (D... 50 Five parts of ≤1μm were mixed with water to prepare ceramic body clay, and the body was formed by rolling. Step 2: After the blank is naturally air-dried, use a mold to press out the delicate eye holes in one go, and carve micro grooves on the surface of the hole wall. The outer diameter of the delicate eye holes is 9mm, the inner diameter is 3mm, the depth of the micro grooves is 40μm, the width is 60μm, and the spacing is 160μm. Then fire it at 680℃. Step 3: Prepare the Linglong glaze slurry and fill the Linglong holes. Place the glazed body in a vacuum environment of ≤5Pa and apply ultrasonic treatment at 30kHz for 15min. The raw material components of the Linglong glaze slurry, by weight, include 20 parts potassium feldspar, 20 parts sodium feldspar, 15 parts quartz, 15 parts kaolin, 8 parts light calcium carbonate, 5 parts calcined zinc oxide, 5 parts calcined boron oxide, 6 parts borax, 4 parts lithium carbonate, 1 part yttrium oxide, 1 part hafnium oxide, and 1 part coated pigment particles (Co-Al pigment, Zr-Si-Pr-V pigment, Ti-Ni pigment). The preparation method of the three colorants is as follows: the three colorants are respectively mixed with boron lithium silicate glass matrix raw materials (SiO2 50%, Al2O3 15%, B2O3 8%, CaO 8%, ZnO 10%, Li2O 2%, Na2O+K2O 7%, particle size D) 50 The pigment particles (0.5-1.5μm) were mixed at a mass ratio of 8:92, pre-melted at 1100℃ for 1.5h, water-quenched, and then pulverized to obtain coated pigment particles. The preparation method of Linglong glaze paste is as follows: add the obtained coated pigment particles to the base glaze paste formed by other raw material components of Linglong glaze paste, stir at 250 rpm for 25 min, and the three colors including pigment particles are prepared into Linglong glaze pastes for use.
[0022] Step 4: Apply a transparent glaze to the inner and outer surfaces of the blank. The raw material components of the glaze, by weight, include 22 parts potassium feldspar, 22 parts sodium feldspar, 18 parts quartz, 10 parts kaolin, 6 parts light calcium carbonate, 4 parts calcined zinc oxide, 5 parts borax, and 1.5 parts lithium carbonate. Step 5: Paint blue and white patterns on the surface of the blank, using Zhuming material (CoO content of about 10%). Step Six: Fire the green body once at 1250-1320℃ in a reducing atmosphere (CO 3%). The firing process uses a gradient temperature increase / decrease, specifically as follows: Ambient temperature - 600℃: Heating rate 100℃ / h; 600-900℃: Heating rate 180℃ / h; 900-1250℃: Heating rate 200℃ / h; 1250-1320℃: Heating rate 60℃ / h; Keep warm at 1320℃ for 35 minutes; 1320-800℃: Cooling rate 120℃ / h; 800-400℃: Cooling rate 25℃ / h; 400-80℃: Cooling rate 100℃ / h.
[0023] Example 2-Example 3 The difference from Example 1 is that the raw materials of the clay body are as shown in Table 1, while the rest are the same as in Example 1.
[0024] Table 1 Raw materials (parts) for body clay
[0025] Examples 4-5 The difference from Example 1 is that the raw materials for the Linglong glaze are shown in Table 2, while the rest are the same as in Example 1.
[0026] Table 2 Raw materials (parts) for Linglong glaze paste
[0027] Examples 6-7 The difference from Example 1 is that the raw materials for the transparent glaze are as shown in Table 3, while the rest are the same as in Example 1.
[0028] Table 3 Raw materials (parts) for transparent glaze
[0029] Examples 8-9 The difference from Example 1 is that the specifications of the eye hole are shown in Table 4, while the rest are the same as in Example 1.
[0030] Table 4 Specifications of the fine eye hole
[0031] Examples 10-11 The difference from Example 1 is that the heating / cooling rate of the firing process is shown in Table 5, while the rest is the same as in Example 1.
[0032] Table 5 Heating / cooling rates during firing process
[0033] Comparative Example 1 The difference from Example 1 is that the raw materials of the clay body are as shown in Comparative Example 1 in Table 1, and the rest are the same as in Example 1.
[0034] Comparative Example 2 The difference from Example 1 is that the raw materials of the Linglong glaze are as shown in Comparative Example 2 in Table 2, while the rest are the same as in Example 1.
[0035] Comparative Example 3 The difference from Example 1 is that the raw materials of the Linglong glaze are as shown in Comparative Example 3 in Table 2, while the rest are the same as in Example 1.
[0036] Comparative Example 4 The difference from Example 1 is that the raw materials of the transparent glaze are, by weight, 45 parts of Yingkou feldspar, 9 parts of Sanbaopeng porcelain stone, 13 parts of Donghai quartz, 12 parts of Guangfeng talc, 6 parts of zinc oxide, and 15 parts of calcite (refer to patent CN115772026A Transparent Glaze II), and the rest are the same as in Example 1.
[0037] Comparative Example 5 The difference from Example 1 is that the raw materials for the boron-lithium silicate glass matrix are SiO2 58%, Al2O3 15%, CaO 8%, ZnO 10%, Li2O 2%, Na2O+K2O 7%, and the particle size D 50 The thickness is 0.5-1.5 μm, and other parameters are the same as in Example 1.
[0038] Comparative Example 6 The difference from Example 1 is that the colorant of the Linglong glaze paste is directly added to the Linglong base glaze; otherwise, it is the same as in Example 1. Comparative Example 7 The difference from Example 1 is that the inner and outer diameters of the eyelet are both 6mm, and the hole wall has no microgrooves; otherwise, it is the same as Example 1. Comparative Example 8 The difference from Example 1 is that in step three, after filling in the Linglong glaze, it only needs to stand for 20 minutes; otherwise, it is the same as Example 1.
[0039] The difference between Comparative Example 9 and Example 1 is that the heating / cooling rate of the firing process is as shown in Comparative Example 9 in Table 5, while the rest is the same as Example 1.
[0040] Comparative Example 10 The difference from Example 1 is that the firing process is to directly heat to 1320℃ and hold for 2 hours, then directly cool down; otherwise, it is the same as Example 1.
[0041] Test case 1. The coefficients of thermal expansion of the body, glaze, and transparent glaze of Examples 1 and 1-4 were measured, and the results are shown in Table 6. The coefficients of thermal expansion were tested in accordance with the relevant standard GB / T 16535-2008.
[0042] Table 6. Coefficient of thermal expansion (×10) -6 / ℃)
[0043] As can be seen from the results in Table 1, this invention, by optimizing the formulations of the body, the delicate glaze, and the transparent glaze, controls the difference in the coefficients of thermal expansion among the three components to within 0.3 × 10⁻⁶. -6 Within a certain temperature range, it can effectively alleviate the stress between the three components, improve the matching degree, and reduce the risk of cracking during the firing process.
[0044] 2. The blue and white porcelain prepared in Example 1 and Comparative Examples 1-10 were observed, and the results are shown in Table 7, with some references to the relevant standards of GB / T 10812-2021.
[0045] Table 7 Appearance
[0046] 3. The light transmittance, thermal stability and yield of the blue-and-white openwork porcelain prepared in Example 1 and Comparative Examples 1-10 were tested. The results are shown in Table 8, with some references to the relevant standards of GB / T 10812-2021.
[0047] Table 8 Performance Results
[0048] As can be seen from the results in Tables 2 and 3, the blue-and-white openwork porcelain prepared using this invention has a bright glaze, a smooth glaze layer, and flat, transparent, bubble-free, and uniformly colored openwork eyes. Different openwork eyes display multiple colors, including blue, green, and yellow, achieving multi-colored openwork eyes within the same piece while maintaining thermal stability, high transparency, and high yield. In contrast, the quality of comparative examples 1-2 and 4 was affected by the mismatch in thermal expansion coefficients between the body, surface glaze, and openwork glaze, resulting in a significant decrease in yield. In Comparative Example 3, the absence of hafnium oxide in the glaze resulted in a small number of bubbles and crystals, affecting transparency. In Comparative Example 5, the boron-lithium silicate glass matrix lacked boron oxide, leading to relatively poor bonding between the colorant and the glaze layer, thus affecting overall transparency. In Comparative Example 6, the colorant was directly added to the glaze, causing the color to easily scatter outside the glaze eye area, affecting the overall aesthetics. In Comparative Example 7, the glaze eye holes used the same diameter for both inner and outer holes, resulting in poor adhesion between the glaze and the body, making it prone to peeling and causing some depressions, thus affecting product quality. In Comparative Example 8, the lack of ultrasonic-assisted vacuum degassing resulted in numerous bubbles, directly affecting the light transmittance of the glaze eye and product quality. In Comparative Example 9, the rapid cooling in the later stages caused the body to shrink sharply, resulting in insufficient stress release and a tendency to crack. In Comparative Example 10, direct heating and calcination were used, which negatively impacted product quality.
[0049] In summary, this invention optimizes the composition of the body, surface glaze, and translucent glaze, matching their coefficients of thermal expansion to a value within 0.3 × 10⁻⁶. -6 Within a temperature range of / ℃, the transparency and yield are effectively improved. At the same time, by designing the structure of the exquisite eye holes and the release method of the pigment, the adhesion between the exquisite glaze and the body and the uniformity of the color are further improved. This process effectively solves the technical defects of the exquisite eye, such as single color tone, poor transparency and low yield. The resulting products are of good quality, have a high yield, and have both artistic and economic value.
[0050] Finally, it should be emphasized that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention can have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing blue and white openwork porcelain, characterized in that, The preparation method includes the following steps: Step 1: Prepare ceramic body clay and roll it into a body; the body clay, by weight, includes 40-55 parts kaolin, 15-20 parts quartz, 15-20 parts potassium feldspar, 3-5 parts talc, and 4-8 parts β-nepheline. Step 2: After the blank is naturally air-dried, use a mold to press out delicate eye holes in one go, and carve micro grooves on the surface of the hole wall. Then fire it at 650-850℃. Step 3: Prepare the delicate glaze paste and fill it into the delicate eye holes. After filling, use ultrasonic-assisted vacuum removal to make the glaze surface smooth. The raw material components of the delicate glaze paste, by weight, include 18-22 parts potassium feldspar, 18-22 parts sodium feldspar, 12-16 parts quartz, 10-20 parts kaolin, 6-10 parts light calcium carbonate, 4-6 parts calcined zinc oxide, 3-6 parts calcined boron oxide, 5-8 parts borax, 3-5 parts lithium carbonate, 0.5-2 parts yttrium oxide, 0.3-1.5 parts hafnium oxide, and 0.8-2 parts coated colorant particles. Step 4: Apply a transparent glaze to the inner and outer surfaces of the blank; the raw material components of the transparent glaze, by weight, include 20-25 parts potassium feldspar, 20-25 parts sodium feldspar, 15-20 parts quartz, 8-14 parts kaolin, 5-8 parts light calcium carbonate, 3-5 parts calcined zinc oxide, 4-6 parts borax, and 1-2 parts lithium carbonate. Step 5: Draw blue and white patterns on the surface of the blank; Step Six: Fire the green body once at 1250-1320℃; Among them, the difference in the coefficient of thermal expansion among the body, the transparent glaze, and the openwork glaze is ≤0.3×10. -6 / ℃.
2. The method for preparing blue-and-white openwork porcelain according to claim 1, characterized in that, In step three, the outer diameter of the exquisite eye hole is 8-12mm, the inner diameter is 2-5mm, and the depth of the microgroove is 30-60μm, the width is 50-80μm, and the spacing is 150-200μm.
3. The method for preparing blue-and-white openwork porcelain according to claim 1, characterized in that, In step three, the coated colorant particles are composed of colorants encapsulated within a borosilicate glass matrix; the chemical composition of the borosilicate glass matrix, by mass percentage, is: SiO2 45-55%, Al2O3 12-19%, B2O3 5-10%, CaO 3-12%, ZnO 5-12.5%, Li2O 1-3%, Na2O+K2O 2-8%, and the particle size D... 50 The range is 0.5-1.5μm.
4. The method for preparing blue-and-white openwork porcelain according to claim 3, characterized in that, The colorant is selected from at least three of the following, and each colorant is individually coated: Royal Blue: Co-Al pigment; Emerald Green: Zr-Si-Pr-V pigment; Golden yellow: Zr-Si-Pr pigment; Pale yellow-green: V-Zr-Si pigment; Bright yellow: Ti-Ni pigment.
5. The method for preparing blue-and-white openwork porcelain according to claim 4, characterized in that, In step three, the preparation process of the Linglong glaze paste is as follows: the colorant and boron lithium silicate glass matrix raw material are mixed at a mass ratio of 2-10:90-98, pre-melted at 950-1150℃ for 1-2 hours, water-quenched and then pulverized to obtain coated colorant particles; the obtained coated colorant particles are added to the base glaze paste formed by other raw material components of the Linglong glaze paste, and stirred at 200-300 rpm for 20-30 minutes to obtain the final product.
6. The method for preparing blue-and-white openwork porcelain according to claim 1, characterized in that, In step three, the ultrasonic-assisted vacuum degassing process is as follows: the blank filled with Linglong glaze is placed in a vacuum environment of ≤5Pa and subjected to ultrasonic treatment of 20-40kHz for 10-20min.
7. The method for preparing blue-and-white openwork porcelain according to claim 1, characterized in that, In step six, under a reducing atmosphere, the firing process employs a gradient temperature increase / decrease, specifically as follows: Room temperature - 600℃: Heating rate 80-120℃ / h; 600-900℃: Heating rate 150-200℃ / h; 900-1250℃: Heating rate 180-220℃ / h; 1250-1320℃: Heating rate 40-80℃ / h; Hold at 1320℃ for 30-40 minutes; 1320-800℃: Cooling rate 100-150℃ / h; 800-400℃: Cooling rate 20-30℃ / h; 400-80℃: Cooling rate 80-120℃ / h.
8. A blue-and-white openwork porcelain prepared by the preparation method according to any one of claims 1-7.
Citation Information
Patent Citations
Exquisite glaze, exquisite ceramic and preparation process of exquisite ceramic
CN101875567B
A method for preparing polychrome openwork porcelain
CN110981417B